Hydrological and thermal responses of seeds from four co-occurring tree species from southwest Western Australia - Rajapakshe, Rajapakshe P.V.G.S.W.; Turner, Shane R.; Cross, Adam; Tomlinson, Sean (OXFORD UNIV PRESS, 2020)
Seed germination is a critical stage in the life cycle of most plants and is defined by specific tolerance thresholds beyond which rates and success of germination rapidly decline. Previous studies have demonstrated that widespread plant species commonly germinate over a broad range of temperatures and water stress levels, whereas range-restricted species often exhibit a narrower germination window in terms of temperature and moisture. We investigated the relationships of the key germination traits of maximum germination (Gmax) and time to 50% germination (t50) in response to temperature (5-35°C) and water stress (-1.5-0 MPa) in four co-occurring Western Australian native Eucalyptus species with widely varying biogeography. Eucalyptus caesia subsp. caesia and E. ornata exhibit a highly localized distribution and a narrow geographical range, being restricted either to granite outcrops or the upper slopes and tops of lateritic rises, respectively. These two species were compared with the two widespread and dominant congenerics E. salmonophloia and E. salubris. There was a distinctive hump-shaped response of t50 to temperature and an exponential response to water stress, characteristic of rate- and threshold-limited processes, but no consistent pattern in the response of Gmax. The four species were significantly different in their thermal performance of t50, with E. caesia and E. ornata displaying narrower thermal tolerance ranges than the two widespread species. In terms of mean final germination percentage, the two range-restricted endemic taxa exhibited higher lability in their response to thermal stress and drought stress compared to the two broadly distributed congenerics. These findings indicate a link between distributional extent, temperature and water stress tolerance and may have implications for identifying ecological filters of rarity and endemism.